2019
DOI: 10.1111/jace.16499
|View full text |Cite
|
Sign up to set email alerts
|

(Na1/2Bi1/2)TiO3‐based lead‐free co‐fired multilayer actuators with large strain and high fatigue resistance

Abstract: Large‐strain multilayer actuators (MLAs) were fabricated by tape‐casting 0.91(Na1/2 Bi1/2)TiO3–0.06BaTiO3–0.03AgNbO3 (NBT‐BT–3AN) lead‐free incipient piezoceramics co‐fired with Pt inner electrodes. Microstructures, dielectric properties, unipolar and bipolar strain, as well as fatigue properties of the MLAs were investigated. It was found that the actuator consisting of 15 ceramic layers with individual thicknesses of 114 μm could output a large unipolar strain of 0.3% and a dynamic displacement of 5 μm at 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…The strain of bulk ceramics can reach 0.20% at 4 kV/cm, while that of MLCA sample is 0.18%. The large coercive electric field and relatively low strain in MLCA sample are consistent with the effect of the mechanical constraint and the induced stress caused by the interface contact between the ceramic and electrode layers during sintering process [2,25,29]. Besides, the inner electrode area is smaller than the sample's cross-section for insulation purpose.…”
Section: J U S T a C C E P T E Dsupporting
confidence: 70%
“…The strain of bulk ceramics can reach 0.20% at 4 kV/cm, while that of MLCA sample is 0.18%. The large coercive electric field and relatively low strain in MLCA sample are consistent with the effect of the mechanical constraint and the induced stress caused by the interface contact between the ceramic and electrode layers during sintering process [2,25,29]. Besides, the inner electrode area is smaller than the sample's cross-section for insulation purpose.…”
Section: J U S T a C C E P T E Dsupporting
confidence: 70%
“…In order to extend materials' applicability to modern electronics, the information on local structure and physical properties is of great interest for fundamental studies. 1,2 It is reported that a re-entrant relaxor behavior is presented in BaTiO 3 -BiScO 3 , BaTiO 3 -Bi(Zn 2/3 Nb 1/3 )O 3 , and (K 0.5 Na 0.5 ) NbO 3 -(Na 1/2 Bi 1/2 )TiO 3 . [3][4][5] Meanwhile, the similar behaviors have been reported in Pb/Bi-based perovskites, such as (Ba 0.925 Bi 0.05 )(Ti 1-x/100 Sn x/100 )O 3 and Pb 0.76 Ca 0.24 TiO 3.…”
Section: Introductionmentioning
confidence: 99%
“…In order to extend materials' applicability to modern electronics, the information on local structure and physical properties is of great interest for fundamental studies . It is reported that a re‐entrant relaxor behavior is presented in BaTiO 3 –BiScO 3 , BaTiO 3 –Bi(Zn 2/3 Nb 1/3 )O 3 , and (K 0.5 Na 0.5 )NbO 3 –(Na 1/2 Bi 1/2 )TiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Until 2014, researchers successfully prepared two-dimensional black phosphorus field-effect transistors [1], and then people discover black phosphorus has great application potential in energy storage devices, optoelectronic devices, photocatalysis, biosensing, etc. [2][3][4][5][6][7][8][9][10][11][12]. Later, based on black arsenic phosphorus (B-AsP) research, an international research group from Germany and the United States made field-effect transistors using a new method that does not require high pressure to synthesize B-AsP, which can reduce the energy of the manufacturing process, thereby reducing costs [13].…”
Section: Introductionmentioning
confidence: 99%